Loss of MLH1 sensitizes colon cancer cells to DNA‐PKcs inhibitor KU60648. Issue 7 (10th March 2017) - Hinrichsen, Inga; Ackermann, Anne; Düding, Tonja; Graband, Annika; Filmann, Natalie; Plotz, Guido; Zeuzem, Stefan; Brieger, Angela
Abstract : Germline mutations of MLH1 are responsible for tumor generation in nearly 50% of patients with Lynch Syndrome, and around 15% of sporadic colorectal cancers show MLH1‐deficiency due to promotor hypermethylation. Although these tumors are of lower aggressiveness the benefit for these patients from standard chemotherapy is still under discussion. Recently, it was shown that the sensitivity to the DNA‐PKcs inhibitor KU60648 is linked to loss of the MMR protein MSH3. However, loss of MSH3 is rather secondary, as a consequence of MMR‐deficiency, and frequently detectable in MLH1‐deficient tumors. Therefore, we examined the expression of MLH1, MSH2, MSH6, and MSH3 in different MMR‐deficient and proficient cell lines and determined their sensitivity to KU60648 by analyzing cell viability and survival. MLH1‐dependent ability of double strand break (DSB) repair was monitored after irradiation via γH2AX detection. A panel of 12 colon cancer cell lines, two pairs of cells, where MLH1 knock down was compared to controls with the same genetic background, and one MLH1‐deficient cell line where MLH1 was overexpressed, were included. In summary, we found that MLH1 and/or MSH3‐deficient cells exhibited a significantly higher sensitivity to KU60648 than MMR‐proficient cells and that overexpression of MLH1 in MLH1‐deficient cells resulted in a decrease of cell sensitivity. KU60648 efficiency seems to be associated with reduced DSB repair capacity. Since the molecular testing of colon tumors for MLH1 expression is a clinical standard we believe that MLH1 is a much better marker and a greater number of patients would benefit from KU60648 treatment.